Strategic flexibility analysis of HRD research and practice post COVID-19 pandemic. Issue 4 (7th August 2020) - Yawson, Robert
ABSTRACT: While governments, intergovernmental organizations, non-profits, corporations are all aware that disruptions through pandemics and other natural bio-disasters like the COVID-19 pandemic can happen, barely are we proactive about them. Instead, we are always reactive. In a virtual Town Hall meeting of the Academy of Human Resource Development (AHRD) held on 9 April 2020, on the theme 'How is the pandemic a game-changer for HRD?, ' the President of AHRD, Laura Bierema, challenged HRD scholars to determine the possible futures of HRD scholarship post-COVID-19 Pandemic. This article proposes the use of the Strategic Flexibility Framework (SFF) to determine the possible futures of HRD post-COVID-19 pandemic. I first discuss the SFF as a scenario planning and analysis tool. I then developed four scenarios of possible futures for HRD Research and Practice post-COVID-19 pandemic. These scenarios include the 'Meaning of work, ' 'Leadership, ' 'Contactless Commerce & Education, ' and 'Volunteerism.' I conclude by discussing the important opportunities that can serve as intervention points for post-COVID-19 HRD theory, research, and practice.